Association between pica and gastrointestinal symptoms in preschoolers with and without autism spectrum disorder: Study to Explore Early Development. Issue 3 (July 2021) - Fields, Victoria L.; Soke, Gnakub N.; Reynolds, Ann; Tian, Lin H.; Wiggins, Lisa; Maenner, Matthew; DiGuiseppi, Carolyn; Kral, Tanja V.E.; Hightshoe, Kristina; Ladd-Acosta, Christine; Schieve, Laura A.
Abstract: Background: Pica, the repeated ingestion of nonfood items, can result in gastrointestinal (GI) outcomes. Children with autism spectrum disorder (ASD) and other developmental disabilities (DDs) are disproportionately affected by both pica and GI symptoms. Study of the inter-relationship between pica, GI symptoms, and ASD/DD is limited. Objective/Hypothesis: We assessed associations between pica and GI symptoms in preschool-aged children with and without ASD and other (non-ASD) DDs in the Study to Explore Early Development. Methods: Our sample included children with ASD (n = 1244), other DDs (n = 1593), and population (POP) controls (n = 1487). Data to define final case-control status, pica, and GI symptoms were from standardized developmental assessments/questionnaires. Prevalence ratios, adjusted for sociodemographic factors (aPRs), and 95% confidence intervals were derived from modified Poisson regression. Results: Within each group (ASD, DD, POP) and for the total sample, pica was associated with vomiting (aPR for total sample 2.6 [1.7, 4.0]), diarrhea (1.8 [1.4, 2.2]), and loose stools (1.8 [1.4, 2.2]). In the DD group, pica was associated with constipation (1.4 [1.03, 1.9]) and pain on stooling (1.8 [1.2, 2.6]). In analyses of the subgroup without pica, increases in GI symptoms were still evident in the ASD and DD groups compared to POP group. Conclusion: These findings highlight an important adverse effect of pica, GI symptoms, in children with and without ASD and DDs; nonetheless, pica does not fully explain the increased risk for GI symptoms among children with ASD and DDs. These findings inform the specialized healthcare needs of children with ASD and other DDs.